Pemanfaatan Air Limbah untuk Meningkatkan Literasi Numerasi dan Kemampuan Berpikir Kreatif pada Pembelajaran Tematik - Aminin, Istiqomah (Jurnal Didaktika Pendidikan Dasar, 2022)
In facing the challenges of the 21st century, Indonesia’s national education pivots on three main things, namely basic literacy, competence and character quality. Numerical literacy is a basic literacy that must be developed because numeracy literacy can lead students to creative thinking skills. This study aims to improve numeracy literacy and creative thinking skills through the use of wastewater in class VI students of SDN Dinoyo 1. This study uses a qualitative approach to describe empirical facts. The design used in this research is Classroom Action Research. The data analysis of this research used descriptive qualitative analysis. The Research model’s in this study is independent Classroom Action Research. Research instruments include: observation sheets, activity sheets, and documentation. The results showed that the use of waste water can improve numeracy literacy and creative thinking skills. Based on the results of the study, suggestions for the next research are learning by using used water for ablution must pay attention to the time allocation required and learning using used waste water must be accompanied by a learning contract and strict rules.